Concept, Essence, And Types Of Civil Legal Relationship - Qutlimuratov Farxad Qalbaevich; Abdibaeva Jamila Aqpolat qızı (Academia One Publishing, 2024)
This article describes the concept of civil-legal relations, its essence, theories of scientists, types of civil-legal relations, subjects and objects of civil-legal relations
Keywords: civil-legal relationship; subjects of civil-legal relationship; personal legal relations of property and nonproperty nature